Notes for a Marxist museology: the “Frontline” Exhibition (Cadernos de Sociomuseologia, 2018)
The article starts with the verification of the existence of unclarified an intrinsic relationship between Marxism and Sociomuseology. Presenting the elements of connection between the two, mainly through the mediation of the thought of Paulo Freire, the article points out the possible elements of enrichment of Sociomuseology by the open development of a Marxist Museology. It follows then for the presentation of a new concept of dialectical exposition, constructed by the analogy with the writings of Karl Marx and Friedrich Engels, demonstrating the first application of the same in the exhibition Front Line: Women and Men fighting for Human Rights. It also presents other concepts that have developed in this process: Museology of the Urgency (opposed to the concept of Alienated Museology), the Militant Museology and the Museology of Guerrilla.Keywords: Sociomuseology; Marxism; Dialectic; Exhibition; Human Rights.